High expression of the Notch ligand Jagged‐1 is associated with poor prognosis after surgery for colorectal cancer. Issue 11 (November 2016) - Sugiyama, Masakazu; Oki, Eiji; Nakaji, Yu; Tsutsumi, Satoshi; Ono, Naomi; Nakanishi, Ryota; Sugiyama, Masahiko; Nakashima, Yuichiro; Sonoda, Hideto; Ohgaki, Kippei; Yamashita, Nami; Saeki, Hiroshi; et al.
Abstract : The importance of Notch signaling in colorectal cancer (CRC) carcinogenesis and progression has previously been presented. Increased expression of Jagged‐1 (JAG1), a Notch ligand, in CRC has been revealed, but the detailed prognostic significance of JAG1 in CRC has not been determined. Protein expression of JAG1 was examined using immunohistochemistry in 158 CRC specimens. Expression of JAG1 and E‐cadherin and their associations with clinicopathologic characteristics, overall survival (OS) and relapse‐free survival (RFS) were evaluated. In vitro studies using compounds to regulate intracellular signaling and small interfering RNA to silence JAG1 were performed in a colon cancer cell line. JAG1 expression in cancerous tissues was weak, moderate or strong in 32%, 36% and 32% of specimens, respectively, and correlated with histologic type and T stage. In multivariate analysis, JAG1 expression, histologic type and lymphatic invasion independently correlated with OS and RFS. The combination of high JAG1 expression and low E‐cadherin expression had an additive effect toward poorer OS and RFS compared with the low JAG1/high E‐cadherin expression subtype. A significant correlation between JAG1 expression and KRAS status was detected in groups stratified as high E‐cadherin expression. In vitro studies suggested that RAS‐MEK‐MAP kinase and the Wnt pathways positively regulated JAG1 expression. Gene silencing with siJAG1 indicated that JAG1 promotes the transition from epithelial to mesenchymal characteristics and cell growth. High expression of JAG1 is regulated by various pathways and is associated with poor prognosis through promoting the epithelial to mesenchymal transition and cell proliferation or maintaining cell survival in CRC. Abstract : This is the first report demonstrating the poor prognostic significance of JAG1 expression in CRC. Combination of high JAG1 expression with low E‐cadherin expression leads to severely poor outcome. Novel insight into the correlation between KRAS status and JAG1 expression in CRC patients.